2017
DOI: 10.1111/vsu.12759
|View full text |Cite
|
Sign up to set email alerts
|

Disposable skin staplers for closure of linear gastrointestinal incisions in dogs

Abstract: Skin staplers provide safe and effective closure of gastrotomies, enterotomies, and colonotomies in dogs. This method is reliable, efficient, and affordable in the hands of veterinary surgeons with varying skill levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(58 reference statements)
2
7
0
Order By: Relevance
“…10 Other studies showed that the presence of foreign bodies was a risk factor for dehiscense, although there is a conflict in this finding among several studies. 6,7,12,56 In this study, both foreign bodies and dehiscence were most common within the jejunum, which was consistent with prior studies. Moreover, previous studies revealed gastrointestinal ulceration is more common in the proximal gastrointestinal tract, especially in the stomach.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…10 Other studies showed that the presence of foreign bodies was a risk factor for dehiscense, although there is a conflict in this finding among several studies. 6,7,12,56 In this study, both foreign bodies and dehiscence were most common within the jejunum, which was consistent with prior studies. Moreover, previous studies revealed gastrointestinal ulceration is more common in the proximal gastrointestinal tract, especially in the stomach.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, the reasons of the original surgery for the cases with dehiscence were not recorded in the present study, although foreign bodies were the most common reason for enterotomy or enterectomy in prior studies. 6,8,56 A previous study reported that linear foreign bodies were most common between the stomach and jejunum, whereas nonlinear foreign bodies were most common within the jejunum. 57 Another study showed that enterotomy was most commonly performed at the jejunum for foreign body retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Linear GI incisions were closed in 333 dogs, with a dehiscence rate of rate of only 1.2%. However, the staples anchored a linear foreign body in two cases . The method was also used to close GI incisions in 29 cats without apparent dehiscence …”
Section: Selection Of Closure Methodsmentioning
confidence: 99%
“…The use of surgical stapling devices for intestinal anastomosis have also been described. There are several variants of realization: evertingend-to-end anastomosis using a triangulation technique and linear stapler (TA -thoracoabdominal) [35]; inverting-everting -functional end-to-end stapled anastomosis -FEESA [1,18,36,37,38,39,40,41]; inverting -circular EEA Staplers [17,42] and skin staples approximating anastomoses [14,43,44,45,46]. The intestinal staplers do induce inversion or eversion [2,15,47].…”
Section: Introductionmentioning
confidence: 99%